Internal Wave Dynamics Over Isolated Seamount and Its Influence on Coral Larvae Dispersion - Stashchuk, Nataliya; Vlasenko, Vasiliy (Frontiers in Marine Science, 2021)
The internal wave dynamics over Rosemary Bank Seamount (RBS), North Atlantic, were investigated using the Massachusetts Institute of Technology general circulation model. The model was forced by M2-tidal body force. The model results are validated against the in-situ data collected during the 136th cruise of the RRS `James Cook' in June 2016. The observations and the modeling experiments have shown two-wave processes developed independently in the subsurface and bottom layers. Being super-critical topography for the semi-diurnal internal tides, RBS does not reveal any evidence of tidal beams. It was found that below 800m depth, the tidal flow generates bottom trapped sub-inertial internal waves propagated around RBS. The tidal flow interacting with a cluster of volcanic origin tall bottom cones generates short-scale internal waves located in 100m thick seasonal pycnocline. A weakly stratified layer separates the internal waves generated in two waveguides. Parameters of short-scale sub-surface internal waves are sensitive to the season stratification. It is unlikely they can be observed in the winter season from November to March when seasonal pycnocline is not formed. The deep-water coral larvae dispersion is mainly controlled by bottom trapped tidally generated internal waves in the winter season. A Lagrangian-type passive particle tracking model is used to reproduce the transport of generic deep-sea water invertebrate species.